Understanding the suicidal moment in adolescence. (18th October 2013) - Miranda, Regina; Shaffer, David
Abstract : Suicide attempts are more common in adolescence than in any other time in life, despite the low prevalence of actual suicide deaths among adolescents. Studies of adolescent suicide risk tend to focus on factors such as psychiatric diagnosis—particularly depression—and history of previous suicide attempts in predicting risk of future suicidal behavior. However, given that a large number of adolescent suicides are first‐time attempts, understanding the circumstances that precede suicide attempts—including the nature of suicidal ideation and of the cognitive and emotional responses that precede ideation—is a critical part of preventing a potentially lethal attempt. We review the psychological precipitants that may inform how suicidal thoughts are transferred into action and examine the risk conferred by having a history of previous suicide attempts and ideation.